IgG subclass deficiencies in children: Facts and fiction. Issue 6 (7th August 2017) - Wahn, Volker; von Bernuth, Horst
Abstract: The chance to analyse the four IgG subclasses arose with the publication of Terry and Fahey 1 . Since then, a lot of new information on the role of subclasses and their deficiency states in humans has been obtained. This review tries to analyse critically our current knowledge of subclass deficiencies in children.